A Relative Age Effect (RAE) analysis of top European football clubs segmented by ownership models - Benito Pérez-González; Pablo Cardona-Soriano; Jose Torres Pru\~nonosa (Cogent Business & Management, 2023)
The aim of this paper is to analyse the Relative Age Effect (RAE) on European elite football teams segmented by type of ownership. The study presents the RAE incidence in the Academy of the UEFA top 10 ranking clubs near the conclusion of the 2020-21 season. The sample (n = 746) comprises players aged 17 to 23 years of age. The frequency of the players' date of birth adjusting to a Poisson regression was used in order to confirm the presence of RAE. The existence of RAE in the whole sample was verified (p < 0.001). By segmenting the sample, the existence of RAE in the analysed age range between U17-19 and U20-23 (p < 0.001) was confirmed. Whereas listed clubs, clubs owned by private shareholders and clubs owned by members had a very significant RAE incidence (p < 0.001), clubs owned by public organisations did not present RAE. Results suggest that the management of youth academies differs depending on the ownership model.
Keywords: 650; ownership; Relative Age Effect; shareholders; soccer; youth academy